A patient‐centric pathway for testicular cancer – A multicentre study investigating the uptake of semen cryopreservation and impact on treatment. (28th February 2021) - Scott, Charles; Omar, Kawa; Alnajjar, Hussain M.; Alifrangis, Constantine; Ahmed, Kamran; Muneer, Asif
Abstract: Background: The option of semen cryopreservation following a diagnosis of testicular cancer shows a variable uptake with the option to cryopreserve before surgery often dependent on the preference of the treating clinician and the fertility laboratory resources available. Objectives: To assess whether the introduction of a patient‐centric pathway for managing suspected testicular cancer increases the uptake of semen cryopreservation and the impact of this on surgical waiting times. Materials and methods: A multicentre retrospective analysis of patients treated as part of a patient‐centric pathway was conducted for suspected testicular cancer at two specialist centres within a one‐stop testicular clinic. Clinical information, including semen cryopreservation acceptance rate, time intervals to surgery and CT scan, TNM stage, histology and age, was recorded from an institutional database. Results: Eighty nine patients (median age: 34 years (range: 14–89)) underwent orchidectomy for suspected testicular cancer over a 15‐month period after the introduction of a patient‐centric testicular cancer pathway at two UK centres. The overall uptake of semen cryopreservation was 68.5% ( n  = 61) with all men under the age of 33 years accepting this option. A microdissection oncoTESE was performed in 9/61 (14.8%) patients who attempted cryopreservation but were found to be azoospermic. Pre‐operative CT imaging was completed for 85.4% of patients, and the median time from initial outpatient consultation to orchidectomy was 9 days. Discussion and conclusions: A patient‐centric pathway ensures that the uptake of semen cryopreservation remains high particularly for those men within the common age for paternity. It also identifies men who may benefit from microdissection oncoTESE for complex cases such as tumours in solitary testicles, bilateral tumours or an atrophic contralateral testicle as well as those diagnosed with de novo azoospermia. The additional time taken for semen cryopreservation to be performed did not significantly delay orchidectomy or influence the decisions for adjuvant treatment.